Reducing greenhouse gas emissions from transportation and land use: Lessons from West Coast states - Lewis, Rebecca; Zako, Robert; Biddle, Alexis; Isbell, Rory (Journal of Transport and Land Use, 2018)
Planners and policymakers in the United States increasing-ly recognize climate change as a critical challenge. Because the trans-portation sector accounts for one-third of all greenhouse gas emissions (GHGs) linked to climate change, some states—including California, Oregon, and Washington—have passed legislation to reduce GHGs from transportation. Much of the work to date has focused on model-ing impacts and evaluating performance of different strategies. Instead, this paper focuses on policy adoption and implementation. This re-search relies on document analysis and stakeholder interviews to ex-amine state efforts to reduce GHGs by examining goals, plans, actions, and results. While these states have all established statutory goals to reduce GHGs, planning, implementation, and monitoring vary across states. California and Oregon rely on state- and metropolitan-level planning, while Washington relies on a state approach. California has enacted funding programs to implement strategies to achieve reduc-tions and worked to reduce regulatory barriers to compact develop-ment. All states monitor levels of GHGs, but the impact of plans is often unexamined. Though West Coast states have taken initial steps to enact goals and require scenario plans, states must provide funding or regulatory relief while improving monitoring in order to achieve ambitious goals to reduce GHGs from transportation.